-87+20y+8=6(5y-2)-7

Simple and best practice solution for -87+20y+8=6(5y-2)-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -87+20y+8=6(5y-2)-7 equation:


Simplifying
-87 + 20y + 8 = 6(5y + -2) + -7

Reorder the terms:
-87 + 8 + 20y = 6(5y + -2) + -7

Combine like terms: -87 + 8 = -79
-79 + 20y = 6(5y + -2) + -7

Reorder the terms:
-79 + 20y = 6(-2 + 5y) + -7
-79 + 20y = (-2 * 6 + 5y * 6) + -7
-79 + 20y = (-12 + 30y) + -7

Reorder the terms:
-79 + 20y = -12 + -7 + 30y

Combine like terms: -12 + -7 = -19
-79 + 20y = -19 + 30y

Solving
-79 + 20y = -19 + 30y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-30y' to each side of the equation.
-79 + 20y + -30y = -19 + 30y + -30y

Combine like terms: 20y + -30y = -10y
-79 + -10y = -19 + 30y + -30y

Combine like terms: 30y + -30y = 0
-79 + -10y = -19 + 0
-79 + -10y = -19

Add '79' to each side of the equation.
-79 + 79 + -10y = -19 + 79

Combine like terms: -79 + 79 = 0
0 + -10y = -19 + 79
-10y = -19 + 79

Combine like terms: -19 + 79 = 60
-10y = 60

Divide each side by '-10'.
y = -6

Simplifying
y = -6

See similar equations:

| 21m^6n^10+7m^7n^8= | | x^2-12x-1260=0 | | 7x-3y=33 | | 56-4x=11-3x | | 8m+18n=-4 | | 9-0.34x=1.16x | | 11x^2=33x | | an-7an-1+10an-2=7.3n | | 6.3(x-9)=1-1/2x | | 4a-3a-5=6a-4 | | (1/16X^8Y^4)^3/4 | | -18+4x=x+3 | | 2x^2-8=y | | 3x+11=-17-11 | | -8(0.1x+0.2)-2.1=0.5 | | 3p^2=-5p+112 | | 2/3×?=1/7 | | 3x+11=-17--11 | | (4x+7)+(x+5)+(7x)=180 | | -6x-78=42+2x | | 5x=40a-1/2 | | 7.8x+9.5+7.6x+1.4=133.94 | | 12m^6+8m^4-16m^2= | | 15h^4-10h^3+25h^2= | | -28-4x=27-x | | 42j^2-19j-1=0 | | 0.1x+17.3=x-1.24 | | H(x)=3x^2+24x+40 | | -24+10x=6x+52 | | X^2-10x+25=20 | | (3x+2)+(x-6)+(x-6)=180 | | 12x^3+2x=0 |

Equations solver categories